2014
DOI: 10.12681/mms.859
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Spawning and Nursery Grounds for Deep–water Red Shrimps in the Central Western Mediterranean Sea

Abstract: The presence of spawning and nursery grounds of Aristeids in the central western Mediterranean Sea were investigated using fishery-independent data (trawl surveys, 1994-2012). Spatial distributions were generated for mature animals and recruits, for both spring/summer and autumn data, using an inverse distance-weighted deterministic interpolation. The persistence index was used to identify stable spawning and nursery grounds in the Sardinian slope region for Aristaeomorpha foliacea and Aristeus antennatus. Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…We did not find higher reproductive condition for A. antennatus close to submarine canyons on the middle slope (between ca . 450–700 m) as previously indicated (off Catalonia: Sardà et al., ; off Sardinia: Palmas et al., ), in studies performed, mainly, over commercial grounds. Such studies suggested migrations by mating and spawning at the middle slope, i.e., over fishing grounds.…”
Section: Discussionsupporting
confidence: 74%
“…We did not find higher reproductive condition for A. antennatus close to submarine canyons on the middle slope (between ca . 450–700 m) as previously indicated (off Catalonia: Sardà et al., ; off Sardinia: Palmas et al., ), in studies performed, mainly, over commercial grounds. Such studies suggested migrations by mating and spawning at the middle slope, i.e., over fishing grounds.…”
Section: Discussionsupporting
confidence: 74%
“…This is particularly relevant since most of the overlapping habitats areas are close to the coast and at relatively short distance from coastal fishing ports. This makes these seamounts particularly attractive for fishery exploitation (Sabatini et al, 2011;Palmas et al, 2015;Lauria et al, 2017) and thus easily subjected to one of the most commonly identified impacts on seamounts (Würtz and Rovere, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Suspension feeders and demersal planktivores likely benefit from these high concentrations of primary producers (Vetter et al, 2010). In Whittard Canyon (Celtic Margin of the NE Atlantic), accelerated currents increase the organic matter influx and therefore the availability of food compared to less active areas on the continental slope (Morris et al, 2013;Palmas et al, 2015). In the upper region of Whittard Canyon (∼700 m depth), a very dense assemblage of corals and large bivalves was observed associated with a nepheloid layer that might provide a significant amount of food (Johnson et al, 2013).…”
Section: Canyon Effects On Benthic Sessile Fauna and Infaunamentioning
confidence: 99%